Transition of pediatric patients with bronchiectasis to adult medical care in the Northern Territory: A retrospective chart audit - Schutz, Kobi L.; Fancourt, Nicholas; Chang, Anne B.; Morris, Peter; Buckley, Rachel; Biancardi, Edwina; Roberts, Kathryn; Cush, James; Heraganahally, Subash; McCallum, Gabrielle B. (Frontiers in Pediatrics, 2023)
Background: Bronchiectasis is increasingly being recognized to exist in all settings with a high burden of disease seen in First Nations populations. With increasing numbers of pediatric patients with chronic illnesses surviving into adulthood, there is more awareness on examining the transition from pediatric to adult medical care services. We undertook a retrospective medical chart audit to describe what processes, timeframes and supports were in place for the transition of young people (≥14 years) with bronchiectasis from pediatric to adult services in the Northern Territory (NT), Australia. Methods: Participants were identified from a larger prospective study of children investigated for bronchiectasis at Royal Darwin Hospital, NT, from 2007–2022. Young people were included if they were aged ≥14 years on the 1st of October 2022 with a radiological diagnosis of bronchiectasis on high resolution computed tomography scan. Electronic and paper-based hospital medical records and electronic records from NT Government health clinics and where possible, general practitioner and other medical service attendance were reviewed. We recorded any written evidence of transition planning and hospital engagement from age ≥14 to 20 years. Results: One hundred and two participants were included, 53% were males, most were First Nations (95%) and lived in a remote location (90.2%). Nine (8.8%) participants had some form of documented evidence of transition planning or discharge from pediatric services. Twenty-six participants had turned 18 years, yet there was no evidence in the medical records of any young person attending an adult respiratory clinic at Royal Darwin Hospital or being seen by the adult outreach respiratory clinic. Conclusion: This study demonstrates an important gap in the documentation of delivery of care, and the need to develop an evidence-based transition framework to transition of young people with bronchiectasis from pediatric to adult medical care services in the NT.